Design and initial testing of a high speed 45 kW switched reluctance drive for aerospace application - Bartolo, James Borg; Degano, Marco; Espina, Jorge; Gerada, C. (Institute of Electrical and Electronics Engineers, 2017)
This paper presents innovative research towards the development of a 45 kW high speed switched reluctance drive as an alternative starter-generator for future aero-engines. To perform such a function the machine had to be designed with a very wide constant power-speed range. During engine-start/motoring mode, a peak torque demand of 54 Nm at 8 krpm was met, whilst in generating mode, 19.2-32 krpm, the machine was designed to deliver a constant power of 45 kW. The key enabling feature of the design lies in the novel rotor structure developed so as to allow for such a wide speed range. The results presented, are those measured during the initial testing phase and validate the system design and performance in the low-speed region with the machine operated in starting-mode. The measured machine power density is at 9.8 kW/ltr, whilst the global system efficiency is at 82%.